(untitled) (Journal of the College of Basic Education, 2024)
The term problematic hero is a definitional model for the anxious fictional character who is ideologically and psychologically unstable, who is often the product of the known conflict caused by his society, or who is experiencing a stage of controlling the sovereignty of this society. From Lukács’ point of view, this hero is neither negative nor positive at all. He is a hero who lives in a struggle between the world of the self and reality, and refuses to be in conflict with reality, as the hero has authentic values ​​that he fails to establish in a world, and he lives in a stage of intellectual and moral decadence, dominated by market concepts and values. , Main vocabulary: the Iraqi novel, Ahmed Khalaf, the novel The Great Dream, the novel (Death of the Father).